Analysis of Student Activity Patterns in the Boarding House Towards Leadership Character Formation to Realize Productive Attitudes in the World of Work - Tesalonika, Christiani; Nazhif Kamal; S. Uswatul Hasanah; Arafi, Thoriq; Feti Fatonah (Journal of Scientific Insights, 2025)
Leadership character development is not an instant process, but rather a long-term journey shaped by the environment, daily interactions, and consistent habits. This study aims to analyze how students’ daily activities in dormitories contribute to the formation of leadership traits and productive attitudes essential for entering the professional world. Utilizing a qualitative approach through review, this research examines how dormitory life fosters impactful small habits such as discipline, responsibility, time management, and social interaction. The findings reveal that routine dormitory activities—such as waking up early, maintaining cleanliness, organizing schedules, participating in organizational and spiritual activities—lay a strong foundation for inclusive and effective leadership. The case of PPI Curug Dormitory further reinforces this notion, demonstrating how long-standing routines and value-based living cultivate highly competent individuals ready to thrive in professional environments. Thus, dormitories are not merely places of residence, but strategic spaces for shaping leadership character and a strong work ethic among the younger generation.